Вычислительная оптика: справочник - Русинов М. М. Михаил Михайлович; Грамматин А. П. Александр Пантелеймонович; Иванов П. Д. Петр Дмитриевич; Андреев Л. Н. Лев Николаевич; Агальцова Н. А. Надежда Алексеевна; Ишанин Г. Г. Геннадий Григорьевич; Василевский О. Н. Олег Николаевич; Родионов С. А. Сергей Аронович (Ленинград, Машиностроение, 1984)
Авт. указаны на обороте тит. л.